Zinc-laccase biofuel cell - Ahmad, Abdul Aziz; Othman, Raihan; Yusof, Faridah; Abd. Wahab, Mohd. Firdaus (IIUM Press, 2011)
A zinc-laccase biofuel cell adapting the zinc-air cell design features is investigated. A simple cell design configuration is employed: a membraneless single chamber and a freely suspended laccase in a quasi-neutral buffer electrolyte. The cell is characterised according to its open-circuit voltage, polarization profile, power density plot and discharge capacity at constant current. The biocatalytic role of laccase is evident from the polarization profile and power output plot. Performance comparison between a single chamber and dual chamber cell design is also presented. As anticipated, a single chamber cell design possesses lower power output as compared to the dual chamber cell design due to probably the charge leakage phenomenon. The biofuel cell possesses an open-circuit voltage of 1.2 V and delivered a maximum power density of 0.9 mW/cm2 at current density of 2.5 mA/cm2. These characteristics are comparable to biofuel cell utilising a much more complex system design.